Coordination of Actin- and Microtubule-Based Cytoskeletons Supports Transport of Spermatids and Residual Bodies/Phagosomes During Spermatogenesis in the Rat Testis - Tang, Elizabeth I. (Endocrinology, 2016)
Germ cell transport across the seminiferous epithelium during spermatogenesis requires the intricate coordination of cell junctions, signaling proteins, and both actin- and microtubule (MT)-based cytoskeletons. Although the involvement of cytoskeletons in germ cell transport has been suggested, the precise mechanism(s) remains elusive. Based on growing evidence that actin and MT interactions underlie fundamental cellular processes, such as cell motility, it is unlikely that actin- and MT-based cytoskeletons work independently to regulate germ cell transport in the testis. Using rats treated with adjudin, a potential male contraceptive that disrupts spermatid adhesion and transport in the testis, as a study model, we show herein that actin- and MT-based cytoskeletons are both necessary for transport of spermatids and residual bodies/phagosomes across the seminiferous epithelium in adult rat testes. Analysis of intratubular expression of F-actin and tubulin revealed disruption of both actin and MT networks, concomitant with misdirected spermatids and phagosomes in rats treated with adjudin. Actin regulatory proteins, epidermal growth factor receptor pathway substrate 8 and actin-related protein 3, were mislocalized and down-regulated at the actin-rich anchoring junction between germ and Sertoli cells (apical ectoplasmic specialization) after adjudin treatment. Nonreceptor tyrosine kinase p-FAK-Tyr(407), known to regulate F-actin nucleation via actin-related protein 3, was also mislocalized and down-regulated at the apical ectoplasmic specialization, corroborating the observation of actin cytoskeleton disruption. Additionally, spatiotemporal expression of MT regulatory protein end-binding protein 1, shown to be involved in MT-actin cross talk herein, was also disrupted after adjudin treatment. In summary, spermatid/phagosome transport across the epithelium during spermatogenesis requires the coordination between actin- and MT-based cytoskeletons.